Biotechnological potential of Ulva ohnoi epiphytic bacteria: enzyme production and antimicrobial activities - Hmani, I.; Ktari, L.; Ismail, A.; EL Bour, M. (Frontiers in Marine Science, 2023)
Seaweed surfaces harbor diverse epibiotic bacterial communities with functions related to morphogenesis, host health, and defense. Among seaweed holobionts, culturable strains can represent innovative sources of bioactive compounds and enzymes. The global industrial demand for microbial enzymes is continually growing in order to improve certain manufacturing processes with new perspectives of industrial exploitation. In this regard, the present study focuses on the enzymatic production and the antimicrobial activities of culturable epibiotic bacteria of Ulva from the Tunisian coast. Culturable associated bacteria were isolated and molecular identification was realized by 16S rRNA gene sequencing. For each strain, eight enzymatic activities were investigated: amylase, hemolysis, DNase, cellulase, lecithinase, lipase, gelatinase, and chitinase. The antimicrobial activity of Ulva-associated bacteria was evaluated against seven pathogenic bacteria, Escherichia coli, Vibrio anguillarum, Vibrio alginoliticus, Pseudomonas aeruginosa, Aeromonas hydrophila, Salmonella typhymurium, and Staphylococcus aureus, and one yeast, Candida albicans. The antibiotic resistance of isolated strains was determined for 15 commonly used antibiotics. The phylogenetic analysis revealed that the isolates belonged to Alphaproteobacteria (3), Gammaproteobacteria (5), Actinobacteria (3), and Firmicutes (4) phyllum. The majority of the isolates (66%) produced simultaneously more than one enzyme. Hemolysis was produced by 46.6% of isolates, while DNase was produced by 33% of strains. On the other hand, 13% of strains produced lecithinase, gelatinase, cellulase, and lipase. No chitinase was produced by the isolated bacteria. In addition, 60% of isolates displayed antimicrobial activity against at least one pathogenic strain. All Ulva ohnoi-associated bacteria were resistant to at least seven commonly used antibiotics. These results highlighted the occurrence of several enzymatic activities within Ulva-associated bacteria that can have potential uses in the industrial sector.